Enhancing Storage Efficiency with Class-Based Storage Design: A Lubricant Drum Warehouse Study at PT Patra Logistik - Iskandar, Yelita Anggiane; Alkatiri, Non Firdiyanti (Jurnal Logistik Indonesia, 2025)
Efficient storage is a critical aspect of warehouse management, particularly in industries constrained by limited space, such as lubricant drum storage. PT Patra Logistik, a third-party logistics (3PL) provider for PT Pertamina Lubricants, has faced inefficiencies in its warehouse operations due to an unstructured storage system. The current use of a random storage method has led to increased travel distances for goods movement, difficulty in locating products, and overall layout disorganization. This study aims to redesign the warehouse layout using the Class-Based Storage (CBS) method to minimize the travel distance involved in the picking and storing of goods. The research employed field observations, interviews, and analysis of historical goods movement data from the April-June 2024 period. ABC Analysis was utilized to classify products based on the frequency of inbound and outbound movements. These classifications served as the foundation for developing a more efficient warehouse layout. The results indicate that implementing the CBS method significantly reduced the total travel distance from 164,625 meters to 78,609 meters, a reduction of 86,015 meters. This improvement enhanced operational efficiency by decreasing retrieval time, increasing labor productivity, and optimizing storage space utilization. Furthermore, validation of the new layout design revealed strong support from respondents, with the majority agreeing or strongly agreeing with the proposed system.